Thrips Monitoring in Florida Blueberries - Gary K. England; Elena M. Rhodes; Oscar E. Liburd (EDIS)
ENY-839, a 3-page illustrated fact sheet by Gary K. England, Elena M. Rhodes, and Oscar E. Liburd, describes techniques for monitoring populations of this key pest of both rabbiteye and southern highbush blueberries in Florida. Includes references. Published by the UF Department of Entomology and Nematology, November 2007.